Surgical Treatment of Left Ventricular Aneurysm Combined with Ischemic Mitral Regurgitation Using a Modified Technique - Rudenko, Sergiy A.; Rudenko, Anatoliy V.; Sokur, Sergey A.; Zhyliak, Oleh V.; Klimenko, Larysa A. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. Ischemic mitral regurgitation (IMR) is the second most common cause of mitral regurgitation (MR). IMR occurs in patients with myocardial infarction due to a rupture of the subvalvular apparatus. Pathological remodel-ing, dilatation and dysfunction of the left ventricle (LV) play a significant role in the development of IMR. The presence of a postinfarction LV aneurysm can lead to the development of MR due to dysfunction, relative and true shortening of the papillary muscles. There are various methods of surgical correction of IMR. The aim. To show the effectiveness of surgical treatment of left ventricular aneurysm combined with ischemic mitral regurgitation using a modified technique. Materials and methods. From January 2011 to December 2019, 20 patients with IMR combined with LV aneurysm underwent surgical intervention using a modified technique at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine. According to this technique, access to the mitral valve was performed through the left ventricle. The mean age of the patients was 61.2 ± 10.1 years. Among patients with IMR, the majority were men (60.0%). The overwhelming majority of patients (80.0%) had the history of hypertension. Diabetes mellitus was detected in 35.0% of patients. Mitral ring dilatation was observed in 25.0% (5) of the cases, papillary muscle displacement in 40.0% (8), chords rupture in 15.0% (3), papillary muscle infarction in 20.0% (4) of the cases. All the patients had reduced LV ejection fraction with a mean value of 34.5 ± 7.8%. Results. Aortic cross-clamp time through ventricular access was 112.9 ± 18.7 minutes. The duration of mechanical ventilation was 19.1 ± 20.6 hours. The length of stay of patients in the ICU was 99.2 ± 43.5 hours. There were no signs of acute heart failure in the early postoperative period in one in five patients (20.0%). The rate of degree III heart failure after intervention using the modified technique was 20.0% (4). The study of the incidence of cardiac arrhythmias after combined intervention showed that 85.0% (17) of patients operated using the modified technique had no cardiac arrhythmias. Conclusions. In patients who underwent surgery using the modified technique, the mortality rate was 5.0%. This is 1.6-2.8 times less than that in patients undergoing conventional operation. Postoperative occurrence of arrhythmias is much less common than that described in the literature.